Evaluation of tensile properties of early-age concrete-block masonry assemblages. (10th March 2023) - Abasi, Ali; Sadhu, Ayan; Dunphy, Kyle; Banting, Bennett
Highlights: Properties of early-age mortar and masonry assemblages are investigated. The strength of masonry is negligible until 3–7 h, then increases logarithmically. Finite element modeling is used to address the gaps in the experimental study. Properties of the bond between blocks and mortar are the most critical parameters. Outlier analysis was necessary to minimize variation in the test data. Abstract: Masonry is one of the most traditional and economical modes of construction worldwide. Although many codes and standards are available to evaluate fully-cured masonry assembly properties for the design of masonry structures, there is a gap in understanding the properties of freshly laid masonry and the design of newly constructed unsupported masonry walls. Early-age (within the first seven days) masonry at the construction site possesses reasonably high compressive strength but considerably low flexural tensile strength, making it vulnerable to lateral loads due to wind, earthquake, and adjacent constructions. This has resulted in numerous incidents of structural damage and injury to workers leading to more stringent and conservative construction bracing techniques. In this paper, the tensile properties of early-age concrete block masonry have been assessed by conducting comprehensive numerical and experimental studies on mortar and masonry assemblage. Outlier analysis has been applied to the experimental data to minimize uncertainties and biases. The modulus of elasticity and tensile strength of the masonry assemblages against the curing time has been obtained using a statistical analysis conducted over a large sample size. The results show that the tensile strength of masonry remains nearly insignificant until 3–7 h, then increases logarithmically. It is also observed that the bond between the mortar and blocks is the weakest part of the masonry assemblages, and the failure happens in the unit-mortar interface bond rather than in the fresh mortar. The modulus of elasticity and tensile strength of early-age masonry assemblages are 38% and 18% of the corresponding properties of early-age mortar material alone, respectively. Therefore, the quantification of assembly properties cannot be ascertained from material testing alone within seven days of construction. It is anticipated that the proposed research will provide valuable design properties leading to improved guidelines needed to design control devices (e.g., temporary bracing) for concrete-block masonry construction.